Early Cretaceous continent basalts in the Alxa Block, NW China: geochronology, geochemistry, and tectonic implications. Issue 7 (3rd May 2021) - Hui, Jie; Cheng, Hongyi; Zhang, Jin; Zhang, Kaijun; Qu, Junfeng; Zhang, Beihang
ABSTRACT: NE Asia has experienced Significant extensional events in the Early Cretaceous, including related volcanic rocks, extensional basins, metamorphic core complexes (MCCs), and low-angle detachment faults. Previous studies primarily focused on the eastern North China Craton (NCC); however, the extensional manifestations in the western NCC are poorly studied and the mechanism is still controversial. This study reports Wuliji volcanic clusters in northern Alxa Block, westmost NCC. Geologic mapping shows that the volcanic cluster is mainly composed of dark grey basalts with interlayered pyroclastic rocks showing columnar joints. The youngest LA-ICP-MS zircon U-Pb age is 103 Ma, consistent with the age constrained by fossils in the interlayered sandstones. Though the Wuliji basalts have amounts of captured zircons, the high MgO, TFe2 O3 and low SiO2, along with Nb/U, Nb/Ta, Zr/Hf ratios and positive Nb, Ta anomalies, indicating no contamination of continental crustal materials. These alkaline basalts are characterized by enrichment in light rare earth elements (LREEs) and large ion lithophile elements (LILEs), slightly positive Eu anomalies and no Nb and Ta depletions similar to other volcanic rocks in Alxa Block, implying an affinity with ocean island basalts (OIB). These volcanic rocks could have been derived from the partial melting of spinel lherzolite in an intracontinental rift setting. The basalts in the Alxa Block are slightly younger than basalts in the eastern NCC in the Early Cretaceous. The occurrence of Early Cretaceous basalts and coeval rift basins with various extensional faults in the westmost NCC may have resulted from the eastward movement of mantle materials due to the rollback of the Paleo-Pacific Plate to the east.